Protease Addiction and Synthetic Lethality in Cancer - Freije, Jose M.; Fraile, Julia M.; Lopez-Otin, Carlos (Frontiers in Oncology, 2011)
The “oncogene addiction” concept refers to the dependence of cancer cells on the function of the oncogenes responsible for their transformed phenotype, while the term “non-oncogene addiction” has been introduced to define the exacerbated necessity of the normal function of non-mutated genes. In this Perspective, we focus on the importance of proteolytic enzymes to maintain the viability of cancer cells and hypothesize that most, if not all, tumors present “addiction” to a number of proteolytic activities, which in turn may represent valuable targets of anti-cancer therapies, even without being mutated or over-expressed by the malignant cells.